Spinocerebellar ataxia type 7: Report of an Indian family - Gurusidheshwar M Wali (Annals of Indian Academy of Neurology, 2013)
Spinocerebellar ataxia type 7 (SCA7) is a form of autosomal dominant cerebellar ataxia which is associated with pigmentary retinal degeneration. It is known for its world-wide rarity except in the Scandinavian countries. It is very rarely reported from India and the neighbouring Asian countries . The present report describes the neurogenetic findings of a family of SCA7, from the northern part of Karnataka in South India. It documents the wide intrafamilial phenotypic variability, which could be correlated with the CAG repeat counts and phenomenon of anticipation. Genotype phenotype correlation highlighted certain disparities in comparison with the previous studies. The report highlights the need for multiethnic population studies and the role of genetic counseling and prenatal testing in SCA7 patients.